Effects of the harmful alga Margalefidinium (aka Cochlodinium) polykrikoides on clearance rates of the hard clam, Mercenaria mercenaria - de Silva, Darren; Gobler, Christopher J. (Frontiers in Marine Science, 2023)
Harmful algal blooms (HABs) such as those formed by the ichthyotoxic dinoflagellate, Margalefidinium (aka Cochlodinium) polykrikoides can have adverse effects on bivalves. While M. polykrikoides has caused significant die offs of bivalves and other marine organisms, the Northern quahog or hard clam, Mercenaria mercenaria, is comparatively more resistant to this HAB. This study quantified clearance rates of juvenile hard clams (10-20 mm) exposed to three different North American populations of M. polykrikoides (bloom, strain CP1, strain CPSB-1G) as well as the nonharmful cryptophyte, Rhodomonas salina and the nonharmful dinoflagellate, Gymnodinium aureolum, in single and mixed algal exposures. Multiple biovolume exposures with M. polykrikoides bloom water and R. salina (1,000, 1,500, 3,000 cells mL-1M. polykrikoides biovolume equivalent) were completed to assess the effects of increasing biomass on hard clam clearance rates and selection. Hard clams opened and actively cleared algal mixtures at and below 1,000 M. polykrikoides cells mL-1. During single species exposures, strain CPSB-1G and R. salina were cleared significantly faster than wild M. polykrikoides populations and strain CP1. During mixed exposures, R. salina was cleared significantly faster than CPSB-1G but not other M. polykrikoides populations and there was no difference between hard clam clearance rates of G. aureolum and R. salina. Clearance rates of M. polykrikoides at ≥1,500 cells mL-1M. polykrikoides/R. salina mixtures were not significantly different than zero unlike clearance of those at <1,000 cells mL-1 indicating a density dependent effect of blooms. Collectively, the results demonstrate that hard clams can actively clear M. polykrikoides cells at moderate (≤1,000 cells mL-1) but not elevated (> 1,000 cells mL-1) bloom densities. Given this, and the documented survival of hard clams during blooms, M. mercenaria may be candidate for aquaculture and restoration in regions prone to HABs caused by M. polykrikoides.